Angiotensin‐converting enzyme inhibitors versus angiotensin receptor blockers: New‐onset diabetes mellitus stratified by statin use. (20th October 2021) - Shin, Juyoung; Kim, Hyunah; Yim, Hyeon Woo; Kim, Ju Han; Lee, Suehyun; Kim, Hun‐Sung
Abstract: What is known and objectives: Regardless of statin use, which is known to induce hyperglycaemia, comparative studies on the risk of new‐onset diabetes mellitus (NODM) with angiotensin‐converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs) are needed. This study evaluated the effects of ACEIs and ARBs on NODM in the clinical setting. Methods: This retrospective cohort study utilized electronic medical record data from Seoul St. Mary's Hospital and Seoul National University Hospital from 2009 to 2012. Patients who were prescribed ACEIs or ARBs for the first time (irrespective of concomitant statin use) were followed up for 5 years. Results and discussions: A total of 11, 703 patients were included, 24.9% ( n  = 2916) were taking ACEIs and 75.1% ( n  = 9189) were taking ARBs. Patients on ACEIs had a significantly lower incidence of NODM both with statin use (HR = 0.13, p  < 0.001) and without (HR = 0.15, p  = 0.009) than patients on ARBs. Age ≥60 years (HR = 1.49, p  = 0.010), BMI ≥25 (HR = 1.96, p  < 0.010), use of calcium channel blockers (HR = 1.47, p  = 0.010), and diuretics (HR = 1.48, p  = 0.010) were risk factors for NODM with statin use. What is new and conclusion: Patients taking ACEIs are less likely to develop NODM than patients taking ARBs, irrespective of statin use. Patients' conditions, including the risk of NODM, should be considered before prescribing ACEIs or ARBs. Future randomized clinical trials are needed to clarify further the relationship between ACEIs and ARBs and their effect on NODM. Abstract : Patients taking ACEIs are less likely to develop NODM than patients taking ARBs, irrespective of statin use.